Satisfaction of people at post-working age with pharmacists' health promotion in Poland - Dorota Raczkiewicz; Jakub Owoc; Iwona Bojar; Beata Sarecka-Hujar (BMC, 2024)
Abstract Background The study aimed to analyze how people at post-working age evaluate health promotion conducted for them by pharmacists in community pharmacies in Poland. We also assessed whether this evaluation is correlated with the frequency of health behaviors. Methods The study comprised 712 Polish people at post-working age (retired), including women 60 + and men 65+. Health Behaviors Inventory and authors' Questionnaire for Evaluation of Pharmacists' Health Promotion were used. Results Conducting health promotion by pharmacists in community pharmacies is relevant in the opinion of post-working-aged people (5.8 on average in the scale of 1-10). However, the patients were not satisfied with the reliability (4.7), accessibility (4.7), communicativeness (5.0), and effectiveness (4.6) of health promotion provided by pharmacists for them. The empathy and politeness of pharmacists during health promotion were rated neutrally (5.4, i.e. neither good nor bad). The evaluations of reliability, accessibility, communicativeness, empathy and politeness, relevance, and effectiveness of pharmacists' health promotion did not correlate with age, marital status, place of residence, type of job in the past, or chronic pain currently (p > 0.05). The men evaluated accessibility higher than the women (5.1 vs. 4.6, p = 0.049), but the other domains were evaluated similarly by both genders (p > 0.05). All the domains of pharmacists' health promotion were assessed the better the higher the frequency of health behaviors the post-working aged people was. Conclusions People in post-working age assessed that health promotion conducted by pharmacists in community pharmacies is important, however they were not satisfied with the reliability, accessibility, communicativeness, and effectiveness of health promotion conducted by pharmacists.